Lack of association between drought and mental health in a cohort of 45–61 year old rural Australian women. (11th June 2015) - Powers, Jennifer R.; Dobson, Annette J.; Berry, Helen L.; Graves, Anna M.; Hanigan, Ivan C.; Loxton, Deborah
Abstract: Objective: To evaluate the impact of drought on the mental health of rural Australian women and those in vulnerable sub‐populations: women who were more isolated, poorer and less educated; and women who had histories of chronic disease or poor mental health. Methods: Surveys were mailed in 1996, 1998, 2001, 2004 and 2008 to 6, 664 women born between 1946 and1951 who were participating in the Australian Longitudinal Study on Women's Health. The surveys included the Mental Health Index of the Medical Outcomes Study Short‐Form 36 (MHI). Drought was assessed by linking the latitude and longitude of women's place of residence at each survey to the Hutchinson Drought Index. Associations between MHI and drought were assessed using linear mixed‐models. Results: While 31% of the women experienced drought in 1998 and 50% experienced drought in 2007; experience of droughts was less common in the other years. Although drought varied from survey year to survey year, mental health did not vary with drought conditions for rural women or vulnerable sub‐populations. Conclusions: These findings are contrary to the long‐held assumption that droughts increase mental health problems in Australia. Implications: While similar results may not be true for men, empirical evidence (rather than assumptions) is required on associations between drought and mental health.